A studio tells its story: student-teachers learn differently. Issue 2 (14th March 2016) - Leshem, Shosh
Abstract: The paper presents the story of an experimental learning studio in a teacher education programme at a college in Israel. The study investigates what students found significant in the studio and more specifically, the meanings students attributed to the experiences in the studio and how it constituted a site for learning. Open ended questionnaires distributed to 171 students were used and analysed qualitatively. The analysis indicates that the studio provided students with opportunities to see elements of 'a lesson' from creative ways of looking at teaching and learning. Students revealed capabilities of making inferences and implications to wider phenomena based on theoretical and practical knowledge. Thus transgressing boundaries of segregated disciplines can lead to meaningful learning and more motivated students.